Characteristics of NOR-banded chromosomes of Mangalarga horses - Lui, J. F.; Giannoni, M. A.; Giannoni, M. L.; Tosta, P. A. (My University, 1990)
The nucleolar organizer regions (NORs) of Mangalarga horses were characterized by analysis of NOR-banded metaphase chromosomes according to the technique of Goodpasture and Bloom (Chromosoma 53: 37-50, 1975). NOR banding was detected by silver staining in the telomeric region of the short arm of pair no. 1, in the region adjacent to the centromere of the long arm of pair no. 25 and in the proximal region of the long arm of pair no. 31. Associations of NOR-bearing chromosomal regions occurred in 12% of all metaphases and were frequent between the chromosomes of pair no. 1. Most (52.15%) of the NOR bands appeared on four chromosomes in both males and females. The maximum number of NOR-banded chromosomes was six, though only 11.34% of the cells examined showed this characteristic.
Keywords: animal cell; chromosome analysis; chromosome NOR; female; horse; male; nonhuman; Animalia; Equidae; Equus caballus